Cocoa processing and commercialization : processing plant feasibility study through the use of operation research techniques (2018)
Cocoa harvesting, processing, transformation and commercialization involves a large amount of processes and various interactions among them. A poorly established value chain system leads to low quality cocoa that restrain the producer from getting high revenues in a premium cocoa market. Systematization of the main stages of the cocoa value chain lead to standard processes and better decisions in the overall cocoa transformation process, tending to generate higher profit. To improve cocoa transformation process and generate high operation profits, we propose an end-to-end solution involving operation research techniques and models, including parameter estimation, optimization models for transport and commercialization, and a simulation of the post harvesting process inside a potential cocoa processing plant. At the core of our approach lies a set of interconnected models that use optimization methods, and simulation. These models cover operational (transport allocation), industrial (processing plant), and financial (market dynamics) decisions. We present a robust analysis for the cocoa value chain...